Knight and day [videorecording (DVD)] - Mangold, James; Diaz, Cameron; Cruise, Tom, 1962-; Grace, Maggie, 1983-; Dano, Paul, 1984-; Sarsgaard, Peter; Davis, Viola, 1965-; Mollà, Jordi (Twentieth Century Fox Home Entertainment, 2010)
When a small-town girl named June meets a mysterious stranger, she thinks she's found the man of her dreams. But she soon discovers he's a fugitive super-spy, who thrusts her into a thrilling cat-and-mouse chase that spans the globe. As the bullets and sparks fly, June must decide if her 'Knight' in shining armor is a dangerous traitor or the love of her life.